DEMOGRAPHIC POLICY AND HUMAN RIGHTS: ETHICAL APPROACHES IN THE CONTEXT OF GLOBALIZATION - Khalilov Alisher Abdumannonovich (Bright Mind Publishing, 2025)
This article focuses on the ethical foundations of demographic policy and its dynamic nature in the context of globalization. The impact of state policies on human rights and freedoms under global conditions is analyzed, and the compatibility of demographic governance with ethical standards is examined. In particular, ethical and legal issues are addressed within the scope of birth control policies, migration policies, and factors affecting family institutions. Additionally, the compatibility of demographic policies with human rights in different regions is studied through comparative analysis. The article evaluates contemporary directions of demographic policy based on international legal norms and the perspectives of the UN and other international organizations. The findings of the research substantiate the relevance of ethical approaches and the principle of respecting human rights in the implementation of demographic policies.
Keywords: Demographic policy, ethical standards, globalization, human rights, freedoms, reproductive rights, migration policy, social justice, state policy, population policy, cultural diversity, legal norms, gender equality, international organizations, UN conventions.